Investment and Profitability of Commercial Banks in Nepal - Kharel, Taranath (Dibyajyoti Journal, 2024)
The objective of this study is to analyze the impact of investment on profitability of selected Nepalese commercial banks. This research employs a descriptive and causal comparative research design. Given the impracticality of including all banks, the study focuses on a selected sample of twenty banks, specifically NABIL bank limited and Standard Chartered bank limited, chosen through judgment sampling. Secondary data, including annual reports and various published sources has used for analysis. The research employs statistical tools such as arithmetic mean, standard deviation, coefficient of variation, correlation coefficient, and regression analysis to evaluate and interpret the data. The results indicate that higher NRB Balance and Investment on Security are positively associated with both return on assets (ROA) and return on equity (ROE), suggesting that banks with larger reserves and substantial investments in securities tend to achieve better profitability. Conversely, Loan and Advance to Customers show a strong positive correlation with ROA but a negative correlation with ROE, indicating that while increased lending boosts asset returns, it may reduce returns on equity and investment in securities. Regression analyses further illuminate these relationships. For ROA, Bank Size emerges as the most significant factor, with a strong positive impact, followed by NRB Balance and Loan and Advance to Customers, which also positively influence ROA. Investment on Security, although positively related, has a less pronounced effect.